Formulation and Characteristics of Hydrogel Patch Containing Pineapple Peel (Ananas comosus L.) Ethanol Extract - Anisah Putri Yuana Sari; Putik Titian Citra Hening; Marshanda Nikita; Ahmad Maulana Al Fatah; Fajrina Rizqi Riyadi; Ihsanti Dwi Rahayu (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2024)
Abstract Pineapple peel (Ananas comosus L.) contains bioactive compounds such as flavonoids and the enzyme bromelain, which possess antioxidant, anti-inflammatory, antibacterial, and anticancer properties, and the ability to accelerate wound healing. Hydrogel patches, as a formulation for transdermal delivery, are effective in wound healing due to their hydrophilic properties that maintain moisture and prevent bacterial infection in open wounds. This study aims to develop and test the characteristics of hydrogel patch formulations containing ethanol extracts of pineapple peel with varying concentrations of 10%, 20%, and 30%, compared to a control (hydrogel patch without pineapple peel extract). A series of evaluation tests were conducted to assess the patch characteristics, including organoleptic tests, pH, absorbency, weight uniformity, swelling ratio, patch thickness, and folding endurance. The results showed that the concentration of pineapple peel extract affects the hydrogel patch characteristics. The higher the extract concentration, the darker the patch color, but the pH, absorbency, and swelling ratio decrease. Patches with higher extract concentrations also showed an increase in weight. Absorbency tests indicated that none of the formulas met the acceptance criteria (<10%), with absorbency results of 22.97%, 11.60%, and 21.95% for 10%, 20%, and 30% extract concentrations, respectively, and 23.43% for the control. Swelling ratio and thickness tests showed the best results for the control, followed by the 10%, 20%, and 30% extract concentrations. The folding endurance test showed that the control and 10% extract formula had good results (>300 folds), while higher extract concentrations reduced the folding endurance of the hydrogel patch .Keywords: extract, pineapple peel, hydrogel patch, formulation, patch characteristics